2014
DOI: 10.1016/j.wasman.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Co-composting of livestock manure with rice straw: Characterization and establishment of maturity evaluation system

Abstract: Abstract:Composting is considered to be the primary treatment method for livestock manure and rice straw, and high degree of maturity is the principal requirement for safe land application of composting product. In this study pilot-scale experiments were carried out to characterize the co-composting of livestock manure and rice straw, as well as to establish a maturity evaluation index system for the composts obtained.Two pilot composting piles with different feedstocks were conducted for 3 months: (1) swine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(73 citation statements)
references
References 27 publications
4
63
1
5
Order By: Relevance
“…Chikae et al (22) reported that the NO 3 -N concentration increased with the reduction of NH 4 -N. This result could be explained by the report that bacteria responsible for nitrification were strongly inhibited by temperature greater than 40°C (43); so, nitrate concentration did not change greatly during the active composting stage. Similar findings were reported by Qian et al on co-composting of livestock manure with rice straw (44).…”
Section: Monitoring Of the Chemical Parameters Of Composting Mixturesupporting
confidence: 91%
“…Chikae et al (22) reported that the NO 3 -N concentration increased with the reduction of NH 4 -N. This result could be explained by the report that bacteria responsible for nitrification were strongly inhibited by temperature greater than 40°C (43); so, nitrate concentration did not change greatly during the active composting stage. Similar findings were reported by Qian et al on co-composting of livestock manure with rice straw (44).…”
Section: Monitoring Of the Chemical Parameters Of Composting Mixturesupporting
confidence: 91%
“…The initial pH in swine slurry-woodchip mixes from the HRFF was generally similar to that reported for other decomposed swine slurry bedding mixes and raw manure compost starting materials (Qian et al, 2014;Tiquia et al, 2002;Tirado et al, 2010). Initial and final pH in the FT were slightly lower than that in the ST (Table 1).…”
Section: Initial High-rise Slurry-woodchip MIX Characteristicssupporting
confidence: 80%
“…It has been suggested that the increase in NO 3 -N and concomitant increase in the NH 4 -N:NO 3 -N ratio can be used as one indicator of compost maturity (Parkinson et al, 2004;Qian et al, 2014) and in this study that ratio was a robust indicator. The ratio of NH 4 -N to NO 3 -N was between 0.02 and 0.34 for piles turned 1Â or 3Â weekly.…”
Section: Nitrogen Dynamicsmentioning
confidence: 54%
“…Un primer factor muy importante en el proceso de compostaje es la humedad (H), ya que permite la movilidad de los microorganismos, el transporte de nutrientes y el flujo de oxígeno para mantener las condiciones aerobias (Kulikowska y Gusiatin, 2015). En la figura 1 se muestra un contenido de H alto, por encima del 80% en todos los tratamientos, resultado esperado debido a la hidratación semanal suministrada y a la producción de moléculas de H 2 O en la reacción bioquímica de codigestión aerobia; este resultado es comparable con la humedad de compost obtenido a partir de estiércol de cerdo y estiércol de residuos lácteos con un 81 y 84%, respectivamente (Qian et al, 2014). El contenido de Cz presentó diferencias significativas en todos los tratamientos, el valor más alto se encuentra en el compostaje vegetal con un 25,52±0,01% y más bajo en el compostaje animal-vegetal al 50% de cada uno (AVII), con un 14,39±0,01%.…”
Section: Análisis Fisicoquímicounclassified
“…El contenido de Cz presentó diferencias significativas en todos los tratamientos, el valor más alto se encuentra en el compostaje vegetal con un 25,52±0,01% y más bajo en el compostaje animal-vegetal al 50% de cada uno (AVII), con un 14,39±0,01%. El CO no presentó diferencias significativas en dos de los cuatro tratamientos, de acuerdo a la figura 1, para A y AVI, con valores de 35,78±1,26 y 35,92±1,15%, mientras que V y AVII si poseen diferencias significativas (P 0,05) entre sí y con respecto a los demás, con valores de 33,18±0,81 y 40,46±1,60% respectivamente, siendo las concentraciones mínima y máxima en los tratamientos; esta última es similar para compostajes a partir de estiércol de cerdo y vaca con valores de 42,2±0,45 y 41,1±1,22% respectivamente, y ligeramente superior al compost de paja de arroz con 38,73±0,99% (Qian et al, 2014). Con respecto a la norma (NTC 5167) cumple para el CO, ya que supera el 30%, mientras que el contenido de H supera el 20%, como máximo establecido, debería entonces reducírsele el contenido de agua para así cumplir este parámetro normativo (Icontec, 2004).…”
Section: Análisis Fisicoquímicounclassified